Void fraction and pressure gradient model for an adiabatic symmetric annular developed flow with entrainment. (August 2022) - Mauro, Alfonso William; Viscito, Luca; Revellin, Rémi
Highlights: New model for pressure gradient during symmetric annular flow Simultaneous evaluation of void fraction, entrainment ratio and phase velocities Calibration of the friction factor for the liquid-vapor interface Assessment of existing correlations and comparison with the present method Abstract: This paper presents a new method for the evaluation of the pressure gradient during annular two-phase flow in the presence of entrainment, based on the momentum balance on the liquid film trapped between the wall and the vapor core. The entrained liquid fraction, together with the atomization/deposition rates and shear stresses, are considered with the use of closure equations, in which the interfacial shear stress is calibrated by means of an experimental database. Through the resolution of a simple iterative procedure, the outcomes of the method are both pressure gradient and void fraction. The accuracy of the present model is tested with independent experimental databases from the literature, showing a very good agreement also with respect to existing available methods for pressure gradient and void fraction.